Pharmacokinetics and Pharmacodynamics of Once-Daily Tacrolimus Compared With Twice-Daily Tacrolimus in the Early Stage After Living Donor Liver Transplantation. Issue 6 (December 2018) - Iwasaki, Mami; Yano, Ikuko; Fukatsu, Sachio; Hashi, Sachiyo; Yamamoto, Yuki; Sugimoto, Mitsuhiro; Fukudo, Masahide; Masuda, Satohiro; Nakagawa, Shunsaku; Yonezawa, Atsushi; Kaido, Toshimi; Uemoto, Shinji; et al.
Abstract : Background: This study investigates the pharmacokinetics and pharmacodynamics of tacrolimus using the once-daily (OD) formulation in the early stage after living donor liver transplantation (LDLT) in comparison with those using the twice-daily (TD) formulation. Methods: Nine patients undergoing primary LDLT and treated with the OD tacrolimus formulation were included. The trough blood concentration (C0 ) of tacrolimus was monitored every day for 3 weeks after LDLT. A time course study of the blood tacrolimus concentrations and calcineurin (CN) phosphatase activity in peripheral blood mononuclear cells was performed 3 weeks after LDLT. Pharmacokinetic and pharmacodynamic parameters were compared with previously reported data using the TD formulation. Results: The interindividual variability in the daily dose of tacrolimus was significantly larger in the OD formulation than in the TD formulation ( P < 0.001). In the time course study, the tacrolimus blood concentrations at 4, 8, and 12 hours after administration and the area under the concentration–time curve from 0 to 24 hours (AUC0–24 ) in the OD group were significantly higher than in the TD group, although the C0 was equivalent. In addition, the C0 was not significantly correlated with the AUC0–24 in the OD formulation. The apparent clearance and the pharmacodynamic parameters examined were not significantly different between the OD and TD groups. Conclusions: The C0 monitoring of the OD formulation may not be optimal in patients at the early stage after LDLT because the C0 was not correlated with the AUC0–24 . If clinicians target the same C0 using the OD and TD formulations, the exposure of tacrolimus can be higher in the OD formulation, and excessive immunosuppression should be noted. Particular attention should be paid to the patients in the early stage after LDLT in the use of the OD oral formulation of tacrolimus.